Hidden volcano abyss [videorecording (DVD)] - Pilcher, Jonny (PBS, 2023)
In January 2022, one of the most powerful volcanic eruptions in recorded history rocked the Pacific islands of Tonga, sending shockwaves around the world. Through first-person accounts of the disaster and eyewitness footage, experience the terrifying power of the eruption and the devastating tsunami that struck the shores of Tonga.